2016
DOI: 10.37237/070105
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Competing Needs among Stakeholders: Lessons from the Self-access Language Learning Centre (SALL) of the Chinese University of Hong Kong (Shenzhen)

Abstract: The Chinese University of Hong Kong (Shenzhen), referred to as ‘University’ or ‘CUHK(SZ)’ hereafter, is a newly established private university located in the Longgong District of Shenzhen, which is a special economic zone in the southern part of China. Its first batch of about 300 undergraduate freshmen, all majoring in Business Administration, commenced studies in September 2014. The Self-access Language Learning Centre (‘SALL’ or ‘the Centre’ hereafter), as a unit under the School of Humanities and Social Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…Except for the SAC activities, one more trend of SAC research has also been focused on the need assessment and/ or analysis of SAC. Ng and Gu (2016) investigated the competing needs among stakeholders of SALL in the School of Humanities and Social Sciences (SHSS) Shenzhen and found that SHSS students perceived positively high to the SALL indicating its precise direction. However, students found the insufficient English atmosphere outside the lecturers' room and looked forward to their speaking especially pronunciation to being guided or corrected in SALL.…”
Section: Literature Review Research On Self-access Center (Sac)mentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the SAC activities, one more trend of SAC research has also been focused on the need assessment and/ or analysis of SAC. Ng and Gu (2016) investigated the competing needs among stakeholders of SALL in the School of Humanities and Social Sciences (SHSS) Shenzhen and found that SHSS students perceived positively high to the SALL indicating its precise direction. However, students found the insufficient English atmosphere outside the lecturers' room and looked forward to their speaking especially pronunciation to being guided or corrected in SALL.…”
Section: Literature Review Research On Self-access Center (Sac)mentioning
confidence: 99%
“…Previous related studies on SAC needs analysis have been investigated by Detaramani and Shuk (1999) of undergraduate students from all departments at the City University of Hong Kong and Ng and Gu (2016) who examined the competing needs among SALL stakeholders in China. University of Hong Kong, Shenzhen, Takahashi, et al Al.…”
Section: Introductionmentioning
confidence: 99%